2015
DOI: 10.1001/jamadermatol.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Overlap of Helper T-Cell Subtypes 17 and 22 in Erythrodermic Psoriasis and Atopic Dermatitis

Abstract: IMPORTANCE Psoriasis and atopic dermatitis (AD) are inflammatory diseases thought to be mediated by helper T-cell subtypes 1 and 2 (T H 1 and T H 2), respectively. Although psoriasis and AD show histopathologic differences during chronic disease, they are difficult to distinguish histologically during erythrodermic exacerbations. OBJECTIVE To determine whether the immune phenotype of helper T cells can differentiate erythrodermic psoriasis and erythrodermic AD by studying skin biopsy specimens of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 38 publications
(50 reference statements)
1
64
0
Order By: Relevance
“…Moy et al found perivascular eosinophils in 7 out of 7 biopsies of erythrodermic psoriasis. Although the quantity of eosinophils was not specified and the study sample size was small, 100% of erythrodermic psoriasis biopsies reviewed had eosinophils . In our study, only 1 patient had erythrodermic psoriasis, and his eosinophil count was 0.…”
Section: Discussionmentioning
confidence: 67%
“…Moy et al found perivascular eosinophils in 7 out of 7 biopsies of erythrodermic psoriasis. Although the quantity of eosinophils was not specified and the study sample size was small, 100% of erythrodermic psoriasis biopsies reviewed had eosinophils . In our study, only 1 patient had erythrodermic psoriasis, and his eosinophil count was 0.…”
Section: Discussionmentioning
confidence: 67%
“…Difficulty in distinguishing psoriasis and atopic dermatitis extends to immunological and molecular analyses. Moy et al determined that it was not possible to discriminate between psoriasis and atopic dermatitis based on immunological phenotype during an erythrodermic state, while Choy et al found comparable expression of neutrophil chemoattractant genes between the 2 inflammatory conditions . Taken together, it appears that psoriasis may share greater pathologic and, thereby, histologic overlap with atopic dermatitis than currently recognized.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed AD to be a result of Th2-skewed immune response, specifically the ratio of Th1:Th2 of chronic AD was 0.09. Consistently, most of the CD3 + T cells in biopsy specimens from chronic AD lesions were comprised of Th2 (64.6%), followed by Th17 (30.4%), Th22 (3.3%) and Th1 cells (4.8%) [119]. …”
Section: Immunological Abnormalitiesmentioning
confidence: 94%